Effect of redox conditions on the structure and solubility of sulfur- and selenium-AFm phases. (September 2019) - Nedyalkova, Latina; Lothenbach, Barbara; Renaudin, Guillaume; Mäder, Urs; Tits, Jan
Abstract: In the context of safe radioactive waste disposal, the incorporation of selenium and sulfur, a major competitor for Se, in AFm phases was investigated by synthesizing and characterizing Se(VI)-, Se(IV)-, S(VI)-, S(IV)-, S(II)-AFm phases to account for a range of possible redox conditions in a cement-based repository for low and intermediate level radioactive waste. The X-ray spectra revealed crystalline AFm phases with trigonal or pseudo-trigonal structure. Different interlayer distances (hkl 00l) were observed for the phases described in the hexagonal lattice, whereas no shift of the (hkl 110) diffraction peak was detected. The type of the interlayer anion seems to control the crystal symmetry of the AFm phase. The amount of water in the interlayer depends on the interlayer anion, relative humidity and temperature of exposure. The AFm phases show similar solubility products suggesting that high sulfur concentration in the cement pore solution can decrease Se binding by AFm phases.